Civil control of the military in Zambia - Haantobolo, Godfrey Haamweela Nachitumbi (My University, 2009)
This study of civil control of the military in Zambia was undertaken in order to ascertain why in contrast with many other former British colonies in Africa such as Ghana and Uganda the military in that country has consistently supported the ruling elite and not sought to obtain political power for itself. In answering the question why this was the case, this study used the qualitative methods and analytical concepts of coercive and consensual measures of control, although the two types of measures are often used in combination, as the main tools that determined civil control of the military in four periods, namely the colonial period, the immediate post-independence period, the period of one-party rule, and the period of reinstated multiparty democracy. Using either coercive or consensual measures as our tools of analysis, comparative profiles were constructed of the nature, character and degree of civil control of the military in each period, and how these were reconfigured by the different political transitions that ushered in the four periods. This assisted in ascertaining which elements of civil control of the military remained constant, and which changed. Data was collected from primary and secondary sources, and verified in in-depth interviews with 20 role players. The main findings are that Zambian governments used two main methods to exert civil control over the military. During the colonial period (1900–1963), the dominant method was coercive measures which was reflected in the policies of racial discrimination and implemented through racialised structures like parliament, the executive and the judiciary. Consequently, relations between the government, the military, and white settlers were harmonious, while those with Africans were antagonistic and explosive. Under the Independence Constitution of the First Republic (1964–1972), the use of consensual measures was manifested in the normative frameworks found in non-racial multiparty democracies and spelt out in the constitution and other specific legislation. In the Zambian case, this was supported by the new government’s motto of ‘One Zambia, One Nation’. Under the One-Party Constitution of the Second Republic (1973-1990), the dominant method was largely through the use of coercive measures characteristic of one party states in terms of which military and civil intelligence officers monitored the political activities of all military personnel as well as ordinary civilians. This helped to remove all anti-government elements from the military. Under the Multi-Party Constitution of the Third Republic (1991-2004), the dominant methods were a combination of all good practices inherited from the previous republics but largely through consensual measures which were manifested in the reintroduction of strong parliamentary and executive oversight over defence expenditure and activities. This study concludes that stable civil control of the military in Zambia in the 20th century was as a result of effective use of either coercive or consensual measures or the mixture of the two and this sets Zambia apart from many other African countries. Further more, it is important to emphasize one point on the relevance of this study’s findings for the study of civil-military relations. This is that despite that both these types of measures worked as a solution for Zambia, upon closer scrutiny, civil control of the military cannot be indefinitely secured by coercive means, and that the only sustainable way of securing civil control of the military is to maintain consensual relations between the core ‘triumvirate’ namely: the political authorities/government/ruling elite; the military and military elite; and the citizenry
Keywords: civil control of military; Zambia